The Impact of Presentation Format and Choice Architecture on Portfolio Allocations: Experimental Evidence - Sebastian Bachler; Felix Holzmeister; Michael Razen; Matthias Stefan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
The question of optimal presentation format and choice architecture for investment decisions has gained momentum among researchers, policy makers, and practitioners alike. Motivated by the question how to provide information to investors in a way to improve financial decision-making, we conduct an investment experiment. We implement a 2 2 factorial design to test the effect of presentation format (graphical vs. tabular) and choice architecture/complexity (asset selection vs. predefined portfolios) on decision-making quality. Overall, our results suggest a differential effect of presentation format and choice architecture: Firstly, we find that the graphical presentation format lowers decision-making quality when the environment is more complex (asset selection). Secondly, within graphical presentation, decision quality is higher when the choice architecture is simplified (predefined portfolios). In addition, we find that a simplified choice architecture leads to higher risk-adjusted returns and reduces the relevance of fluid intelligence and numeracy for decision-making quality.
Keywords: G11; G41; G50; 330; Investment Decision; Presentation Format; Choice Architecture; Decision-Making Quality; Experimental Finance; Investment Decision; Presentation Format; Choice Architecture; Decision-Making Quality; Experimental Finance